(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The makeup color industry for women in India is rapidly expanding, fueled by a youthful population, rising disposable income, and the impact of social media. Over the past ten years, there has been a significant shift in how Indian women perceive beauty and personal care. The Indian cosmetics and makeup market is witnessing substantial growth, with forecasts for 2025 and beyond indicating strong compound annual growth rates, although estimates differ by source, with some suggesting around 3.8% (according to Statista for cosmetics) and others indicating potentially over 8-10% (as per Fortune Business Insights and Mordor Intelligence) for the broader market. This growth is propelled by increased disposable income, urbanization, the effects of social media, and a growing preference for natural or herbal products, with major segments such as skincare and color cosmetics leading the way, while premiumization and male grooming also play roles in the industry's expansion.